Contradicciones en la reacción del consumidor ante el polígrafo y perfil de personalidad = Contradictions in consumer reaction to the polygraph and personality profile - Escobar Torres, María Orquídea (Journal of Education, Health and Sport, 2015)
Escobar Torres María Orquídea. Contradicciones en la reacción del consumidor ante el polígrafo y perfil de personalidad = Contradictions in consumer reaction to the polygraph and personality profile. Journal of Education, Health and Sport. 2015;5(11):504-515. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35691 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A504-515 http://pbn.nauka.gov.pl/works/684754 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Escobar Torres María Orquídea. Contradicciones en la reacción del consumidor ante el polígrafo y perfil de personalidad. Quality in Sport. 2015;1(3):50-60. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%283%29%202015%2C%20s.%2050-60 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. María Orquídea Escobar Torres[1] Corporación Universitaria Unitec, Colombia Contradicciones en la reacción del consumidor ante el polígrafo y perfil de personalidad Contradictions in consumer reaction to the polygraph and personality profile Resumen En mercadeo, la información basada en reportes verbales del consumidor puede tener baja confiabilidad, debido a diferentes motivos inconscientes de las personas, que los llevan a reaccionar de manera contradictoria a lo que expresan en sus opiniones. Estas reacciones con frecuencia no se pueden observar de manera directa. La investigación en referencia, buscaba conocer las respuestas psicofisiológicas ante un comercial de TV, medidas por medio del polígrafo, en 20 personas, hombres y mujeres estudiantes universitarios y profesionales, con edades entre 18 y 48 años, en Bogotá. Los resultados mostraron una contradicción entre el reporte verbal sobre el impacto del comercial y las reacciones frente al polígrafo, encontrándose además el perfil de personalidad de aquellas personas que presentaron contradicción. Palabras clave: polígrafo, perfil de personalidad, marketing, comportamiento del consumidor, neuromarketing. Abstract In marketing, the information based on verbal reports consumer may have low reliability due to different unconscious motives of the people who lead them to react contradictory to the views they express. These reactions often cannot be observed directly. The research in question, sought to know the psychophysiological responses to a TV commercial, measured by the polygraph. Involved 20 people, men and women professionals and university students, aged between 18 and 48 years in Bogotá. The results showed a contradiction between verbal report on the impact of commercial TV and reactions to the polygraph, also found the personality profile of those who had contradiction. Key words: polygraph, personality profile, marketing, consumer behavior, neuromarketing. [1] Colombiana. Psicóloga PUJ, Magister en Dirección de Marketing Universidad Viña del Mar, Chile. Especialista en Gerencia de Marketing, UNILATINA. Estudios de Doctorado UNED-Madrid. Docente Investigadora Corporación Universitaria UNITEC, Bogotá, Colombia. orquideaescobar@gmail.com. Tel.(57-1) 7434343 / 3007820935.